The Role of Youth as Non-State Actors in Providing Clean Water and Adequate Sanitation in the Tebas River Based on Quadruple Helix - Zhan, Fuzy Firda; Zhan, Fuza Firdaus (APLIKATIF: Journal of Research Trends in Social Sciences and Humanities, 2023)
For many years, the Tebas River has been the lifeblood of the community in Tebas Kuala Village and Tebas Sungai Village, Tebas District, Sambas Regency, West Kalimantan Province, Indonesia. However, as the population increases, industrial areas and technological developments affect the condition of the river water. Currently, the Tebas River water is starting to be polluted by waste from households and small industries with the presence of E. Coli bacteria due to the continued use of plunge toilets, which has the potential to cause diarrhea. This article aims to analyze the role of youth as non-state actors in providing clean water and adequate sanitation in the Tebas River. The method used in this article is descriptive qualitative with data obtained from observation and literature study. The research results found that stakeholder handling is needed through quadruple helix synergy, namely from government, society, industry, and academia. This management synergy also supports the achievement of the 2030 Village SDGs, especially in point 6, namely Clean Water and Sanitation. In conclusion, this initiative discusses protecting the Tebas River for both the present and the future generations.